The Relationship between Government Debt and Social Welfare - Muhammad Kivlan Reftreka Nugraha; Hefrizal Handra (Jurnal Ekonomi Pembangunan, 2021)
This study aims to analyze the relationship between government debt and social welfare in Indonesia in 1980-2019. The data used in this research is secondary data using time series data. The analysis used is the Error Correction Model (ECM). The findings result from the first model show that in the short-run, additional debt-to-GDP was not significant to the poverty level and GDP per capita. Meanwhile, the long-run, additional debt-to-GDP is significant to the poverty level and GDP per capita. The results also find that in the long run additional debt-to-GDP is positively correlated with poverty levels in Indonesia, meaning that additional debt-to-GDP increases the poverty rate in Indonesia. For GDP per capita, additional debt-to-GDP has a negative correlation. The inflation, tax-to-GDP, and GDP are not significant to the poverty rate in the short-run. Meanwhile, the long run, the additional debt-to-GDP ratio and GDP variable is significant to the poverty rate, and has a positif and negative correlation. The findings from second model also indicate that population and inflation are significant and positively correlated with the poverty level, but tax-to-GDP ratio is not significant on GDP per capita in the short-run. Meanwhile, the long run, the population and tax-to-GDP are significant to GDP per capita. Total population has a positive correlation, while tax-to-GDP ratio has a negative correlation.